الحقيقة القضائية والحقيقة الواقعية بين النسبية والاطلاق: دراسة في ضوء قواعد علم الفلسفة - د. مصطفى إبراهيم الزلمي; د. ياسر باسم ذنون السبعاوي (PROSPECTIVE RESEARCHES, 2023)
t Legal judgments are almost issued according to judicial fact which may be for from reality depending on available evidence presented to the court. The evidence varies due to the evidence system being bound, free, or both, e.g in Iraqi legislation. The present paper has come to auiming at separating judicial fact and reality. The research has come up with the conclusion which says that the nature of the judicial fact is relative and net absolute. That should not be understand as "relative" for only the judicial society, for it is a must, but it means that the judge's realization for the fact and the opposite evidence are tendentious. This makes it relative.